Operative-Search Activities in Combating New Forms of Digital Organised Crime - Kozhabekov, Dauren; Bayseitova, Aliya; Saitbekov, Aidar; Kassymova, Assel; Alimova, Elvira (Law, State and Telecommunications Review, 2026)
[Purpose] The research presents a fundamental theoretical and empirical study of the issues of operational and investigative activities in the context of countering the latest forms of organised crime in the digital space. [Methodology/approach/design] A scientific analysis is made of the conceptual and categorical apparatus and essential characteristics of operational and investigative measures used to detect, document and suppress criminal activity in the context of the digital transformation of society. The methodological foundations and structural elements of the system of operational and investigative measures are examined, with due regard for the specifics of the digital environment and the peculiarities of modern organised criminal groups [Findings] On the basis of a comprehensive comparative legal analysis of Kazakh and international legislation, the peculiarities of regulatory and legal regulation of the activities of operational and investigative units in the field of combating organised crime in the digital space are revealed. Key areas for modernisation of criminal, criminal procedure and operational search legislation are identified to improve the efficiency of law enforcement in the context of digitalisation of crime. In the context of international cooperation, the current state of interaction between law enforcement agencies of different countries in combating transnational organised crime is analysed, promising areas for the development of interstate cooperation and mechanisms for improving its effectiveness are identified. Specific recommendations are formulated for optimising the use of special technical means and information technologies in the process of documenting the illegal activities of organised criminal groups. As a result of the study, the role and importance of operational and investigative units of internal affairs bodies in the system of combating organised crime in the digital space are defined, and scientifically sound proposals for improving their activities are developed. [Practical implications] The recommendations are formulated for modernising the tactics and methods of conducting operational and investigative measures aimed at identifying and documenting new forms of criminal activity in the digital environment. A set of organisational and legal measures is proposed to improve the effectiveness of preventive activities of law enforcement agencies in the field of combating organised crime in the context of the digital transformation of society. [Originality/value] The study provides a longitudinal analysis of cybercrime trends in relation to major global events, and links the rise in cyber incidents to geopolitical and economic disruptions.